Emergence of colistin resistance in extended-spectrum beta lactamase producing Enterobacteriaceae isolated from food animals and its public health implication: A review - Bitrus, Asinamai Athliamai; Chuanchuen, Rungtip; Luangtongkum, Taradon (Journal of Advanced Veterinary and Animal Research, 2018)
Antimicrobial resistance as a result of emergence of extended-spectrum beta lactamase producing Enterobacteriaceae is a major health problem of human and animal that requires an intensive global attention. The production of beta lactamase enzymes remains as one of the major factors contributing to the development of resistance to beta lactams. These enzymes hydrolyze the beta lactam ring of the antibiotic and render it ineffective. Extended-spectrum beta lactamase producing bacteria have the ability to develop resistance to a number of antibiotics including the carbapenem and other third generation cephalosporins. In addition, the recent emergence and dissemination of the colistin resistance determinants mcr-1, mcr-2 and mcr-3 poses a serious threat to colistin as a drug of last resort in human medicine. In this review, we utilized words such as “colistin resistance and Escherichia coli”, “Klebsiella and colistin resistance”, “colistin resistance and Salmonella” as well as “detection of mcr-1 genes in Salmonella and E. coli”. The extended-spectrum beta lactamase producing bacteria under Enterobacteriaceae that are resistant to colistin possess the ability to be transferred resistant determinants to other susceptible cells at a higher frequency. In this paper, the role of manure from food animals and how air travel contributes to the dissemination of mcr-1 haboring bacteria, resistance determinants and other metabolites that constitute a public health problem was also reviewed. It is concluded that these pathogens have significant consequences to the control of infection and plays key roles in treatment failure with colistin. http://doi.org/10.5455/javar.2018.e246